A 1300 mm2 Ultrahigh‐Performance Digital Imaging Assembly using High‐Quality Perovskite Single Crystals. Issue 29 (29th May 2018) - Liu, Yucheng; Zhang, Yunxia; Zhao, Kui; Yang, Zhou; Feng, Jiangshan; Zhang, Xu; Wang, Kang; Meng, Lina; Ye, Haochen; Liu, Ming; Liu, Shengzhong (Frank)
Abstract: By fine‐tuning the crystal nucleation and growth process, a low‐temperature‐gradient crystallization method is developed to fabricate high‐quality perovskite CH3 NH3 PbBr3 single crystals with high carrier mobility of 81 ± 5 cm 2 V −1 s −1 (>3 times larger than their thin film counterpart), long carrier lifetime of 899 ± 127 ns (>5 times larger than their thin film counterpart), and ultralow trap state density of 6.2 ± 2.7 × 10 9 cm −3 (even four orders of magnitude lower than that of single‐crystalline silicon wafers). In fact, they are better than perovskite single crystals reported in prior work: their application in photosensors gives superior detectivity as high as 6 × 10 13 Jones, ≈10–100 times better than commercial sensors made of silicon and InGaAs. Meanwhile, the response speed is as fast as 40 µs, ≈3 orders of magnitude faster than their thin film devices. A large‐area (≈1300 mm 2 ) imaging assembly composed of a 729‐pixel sensor array is further designed and constructed, showing excellent imaging capability thanks to its superior quality and uniformity. This opens a new possibility to use the high‐quality perovskite single‐crystal‐based devices for more advanced imaging sensors. Abstract : A low‐temperature‐gradient crystallization (LTGC) method is developed to fabricate high‐quality perovskite CH3 NH3 PbBr3 single‐crystals with high carrier mobility, long carrier lifetime, ultralow trap‐state density, and superior uniformity. Meanwhile, its application in photosensors gives superior detectivity as high as 6 × 10 13 Jones and response speed is as fast as 40 μs. A large‐area (≈1300 mm 2 ) imaging assembly composed of a 729‐pixel sensor array is further designed and constructed, showing excellent imaging capability thanks to its superior quality.